Mechanical work and physiological responses to simulated cross country mountain bike racing - Macdermid, P. W.; Stannard, S. (Journal of Sports Sciences, 2012)
The purpose was to assess the mechanical work and physiological responses to cross country mountain bike racing. Participants (n = 7) cycled on a cross country track at race speed whilst O2, power, cadence, speed, and geographical position were recorded. Mean power during the designated start section (68.5 ± 5.5 s) was 481 ± 122 W, incurring an O2 deficit of 1.58 ± 0.67 L/ min highlighting a significant initial anaerobic (32.4 ± 10.2%) contribution. Complete lap data produced mean (243 ± 12 W) and normalised (279 ± 15 W) power outputs with 13.3 ± 6.1 and 20.7 ± 8.3% of time spent in high force-high velocity and high force-low velocity, respectively. This equated to, physiological measures for % O2max (77 ± 5%) and % HRmax (93 ± 2%). Terrain (uphill vs downhill) significantly (P < 0.05) influenced power output (70.9 ± 7.5 vs 41.0 ± 9.2% Wmax),the distribution of low velocity force production, O2 (80 ± 1.7 vs 72 ± 3.7%) and cadence (76 + 2 vs 55 ± 4 rpm) but not heart rate (93.8 ± 2.3 vs 91.3 ± 0.6% HRmax) and led to a significant difference between anaerobic contribution and terrain (uphill, 6.4 ± 3.0 vs downhill, 3.2 ± 1.8%, respectively) but not aerobic energy contribution. Both power and cadence were highly variable through all sections resulting in one power surge every 32 s and a supra-maximal effort every 106 s. The results show that cross country mountain bike racing consists of predominantly low velocity pedalling with a large high force component and when combined with a high oscillating work rate, necessitates high aerobic energy provision, with intermittent anaerobic contribution. Additional physical stress during downhill sections affords less recovery emphasised by physiological variables remaining high throughout.